The Taking and Use of Dowry by the Bride's Parents: A Sociological and Islamic Legal Perspective - Adam Muhsin; Dzulfikar Rodafi; Syamsu Madyan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
One form of Islamic respect for women is the provision of a dowry, which is the wife's full property. Essentially, the dowry is an absolute right of the wife. However, in Padurungan Tanah Merah Village, Bangkalan, a predominantly Muslim village, a tradition still exists where the bride's parents take the gift in the form of money and may not use it for the wife. This prompted researchers to examine this issue in more depth using a juridical-empirical approach and qualitative methods using interviews, observation, and documentation. The results of the study revealed three patterns of dowry use by parents: it is considered the full right of the parents, it is distributed to unmarried relatives, or it is used to cover wedding expenses. Sociologically, this practice is motivated by the belief that it is taboo for the bride to use the dowry, although this tradition has no basis and tends to be superstitious (tathoyur). Under Islamic law, this act constitutes the taking of another person's property, which requires the wife's consent (thibi nafsi).